In vivo generated autologous plasmin assisted vitrectomy in young patients - Aras, Cengiz; Şentürk, Fevzi; Koytak, Arif; Doğramacı, Mahmut; Karaman Erdur, Sevil; Kocabora, Selim (BioMed Central Ltd, 2022)
Background Autologous plasmin enzyme facilitates the induction of posterior vitreous detachment(PVD) during vitrectomy in young patients. We proposed the concept of in-vivo generated plasmin which is based on the injection of tissue plasminogen activator(t-PA) and autologous whole blood(AWB) into the vitreous cavity. The purpose of this pilot study is to report the efficacy of preoperative simultaneous intravitreal injection of(t-PA) and autologous whole blood in facilitating the intraoperative induction of PVD in young patients with various vitreoretinal pathologies. Methods Seventeen eyes of 16 young patients with various vitreoretinal pathologies requiring vitrectomy, who received simultaneous intravitreal injection of 0.1 ml of AWB and 25 mu g of t-PA, 3 days prior to surgery were retrospectively reviewed. Outcome measures were the number of attempts required to achieve successful intraoperative separation of the posterior hyaloid; the postoperative visual acuity; and intraoperative and postoperative complications. Results The mean age of the patients was 23.87 +/- 10.09 years, ranging from 10 to 39 years. Eight of 16 patients were men. The mean follow-up time was 19.35 +/- 5.04 months, ranging from 12 to 26 months. Surgical indications for vitrectomy were chronic retinal detachment (n = 7), traumatic retinal detachment without proliferative vitreoretinopathy(n = 3), traumatic macular hole(n = 1), secondary vasoproliferative tumor(n = 4) and optic pit maculopathy(n = 2). Patients with retinal detachment complicated with PVR and those who were older than 40 years of age were excluded from the study. Separation of the Weiss ring from the optic nerve head was achieved intraoperatively in all cases, with a mean number of 2.86 +/- 1.4 attempts. While the mean preoperative LogMAR visual acuity was 1.38 +/- 0.59, ranging from 2.40 to 0.50, it was a mean of 0.51 +/- 0.29, ranging from 1.00 to 0.10 at final postoperative exam(p < 0.001; paired samples t-test). No preoperative or intraoperative complications were noted. Conclusion Preoperative simultaneous intravitreal injection of 25 mu g t-PA with 0.1 ml of AWB facilitates the intraoperative induction of posterior vitreous detachment in young patients.
Keywords: Posterior Vitreous Detachment; Tissue Plasminogen Activator; Autologous Whole Blood